PERBEDAAN MOTIVASI DAN PERSEPSI IBU HAMIL TENTANG PRENATAL YOGA DI PUSKESMAS YANG MENYEDIAKAN DAN YANG TIDAK MENYEDIAKAN PROGRAM PRENATAL YOGA - Ayu Wulandari (STIKes CHMK, 2020)
The participation of pregnant women in physical activities, especially yoga is important during pregnancy, intra partum and post partum period. Motivation and perception factors are considered to influence yoga participation in pregnant women. The purpose of this study was to analyze the differences in motivation and perceptions of pregnant women about prenatal yoga in Public Health Center (PHC) that provide and does not provide prenatal yoga. This research was a comparative analytic study with cross sectional approach. The sample were 108 pregnant women, 54 people who examined their pregnancy at North Denpasar III PHC and 54 people who examined their pregnancy at East Denpasar I PHC. The sampling technique was taken by accidental sampling. Data analysis by using the Mann-Whitney test. The data showed that there was a significant differences between motivation and perceptions of pregnant women who check their pregnancies at PHC that provide and those that does not provide prenatal yoga. It is expected that the PHC as a primary health facility is expected to provide prenatal yoga facilities for pregnant women Key word: Motivation, Perception, Prenatal Yoga, Public Health Center